Application of transcriptomics techniques in skin cancer - Ma, Yuhan; Wang, Fangfang; Xu, Suling (Frontiers in Oncology, 2025)
Skin cancer is one of the most common malignant tumors worldwide, with its mortality rate showing a significant upward trend, thereby increasing the disease burden on patients and society. With the rapid development of next-generation sequencing technology, transcriptomics has revealed complex disease mechanisms by analyzing the expression patterns of differentially expressed genes, providing important tools for exploring the occurrence and development of skin cancer, studying the tumor microenvironment, investigating drug resistance mechanisms, and optimizing treatment strategies for skin cancer. This article aims to briefly summarize the development history of transcriptomics technology, review its research progress in skin cancer, and contribute to a more comprehensive understanding of the mechanisms underlying skin cancer development. It also holds promise for identifying potential therapeutic targets and providing new insights for clinical treatment of skin cancer.